Beam Discovery Signal-Based Beam Selection in Millimeter Wave Heterogeneous Networks - Bo Yin; Yanbo Chen; Zufan Zhang; Mengjun Wang; Shaohui Sun (IEEE Access)
Most beam selection algorithms determine the best beam according to the methods of feedback and exhaustive search in a millimeter wave (mmWave) massive multiple-input multiple-output (MIMO) system. However, the exhaustive search and the redundant feedback will result in high computational complexity. This paper proposes a mmWave massive MIMO beam selection algorithm based on the beam discovery signal (BDS), where each beam transmitted by the mmWave access point is identified by a specific BDS, and the best beam for the user equipment is then determined by detecting the BDS. In addition, in mmWave heterogeneous networks with densely deployed small cells, strong interference beams are determined through inter-cell cooperation, and orthogonal codes are allocated to the optimal beams and strong interference beams to reduce beam interference from adjacent cells. Simulation results show that the proposed algorithm can avoid the computational complexity caused by exhaustive search, thus simplifying the beam selection process. Furthermore, the algorithm can effectively suppress inter-cell beam interference in multi-cell scenario, and the sum-rate can be further increased.